(untitled) (Asian Journal of Pharmaceutics (AJP), 2015)
Zataria multiflora is a medicinal plant that has been interested in antimutagenicity effect because of its high antioxidantÂ activity and richness of flavonoids. Antimutagenicity effect of total extract of the plant has been reported previously.Â Aerial parts of Z. multiflora were extracted by petroleum ether, chloroform and 80% methanol by liquidâ€liquid extractionÂ method consequently. The fractions were concentrated in vacuum and dried at 40Â°C in oven. The genotype of two standardÂ strains of Salmonella typhimurium (TA98, TA100) was confirmed by the evaluation of two important factors of histidineÂ requirement and the presence of R factor. The minimum inhibition concentration (MIC) of the fractions against these two strains was determined by agar dilution method. From each fraction, various concentrations less than MIC were studied for antiâ€mutagenic test. The sample along with bacterial strain and mutagen agent were incubated at 37Â°C for 48 h. TheÂ number of revertant colonies was counted and compared with control plates. Our results showed that all fractions especiallyÂ petroleum ether and chloroform ones maintain the number of colonies in the standard range in control plates and preventÂ from the growth of many strains of bacteria and increase of revertant colonies enhancement in a concentrationâ€dependentÂ manner. This effect was prominent against TA100 starin. Methanolic fraction exhibited antiâ€mutagen activity just in theÂ highest used concentration in the presence of TA98. Key words: Ames test, antiâ€mutagenicity, fraction, phenylpropanoids, Salmonella typhimurium, Zataria multiflora